Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
Step-by-step explanation:
1) 4x -3
x = -7 ;
4x - 3 = 4*(-7) - 3 = - 28 - 3 = -31
x = 14 ;
4x - 3 = 4*14 - 3 = 56 - 3 = 53
x = 0
4x - 3 = 0 - 3 = -3
2) 6 -3x
x = -7 ;
6 - 3x = 6 - 3*(-7) = 6 + 21 = 27
x = 14
6 - 3x = 6 - 3*14 = 6 - 42 = -36
x = 0
6 - 3x = 6 - 0 = 6
[tex]3) \dfrac{3x - 21}{7}\\\\x = -7\\\\\\\dfrac{3*(-7)-21}{7}=\dfrac{-21-21}{7}=\dfrac{-42}{7}=-6\\\\\\x = 14\\\\\dfrac{3*14-21}{7}=\dfrac{42-21}{7}=\dfrac{21}{7}=3\\\\\\x=0\\\\\dfrac{0-21}{7}=\dfrac{-21}{7}=-3\\\\[/tex]
4)
[tex]\dfrac{3x}{7}-21\\\\\\x = -7\\\\\dfrac{3*(-7)}{7}-21=-3-21=-24\\\\\\x =14\\\\\dfrac{3*14}{7}-21=3*2-21=6-21=-15\\\\\\x=0\\\\\dfrac{0}{7}-21=-21[/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.